Intravenous contrast agents in diabetic patients taking metformin; an updated review on current concepts - Masoumeh Asgharpour; Rouzbeh Danialy; Seyedhadi Mirhashemi; Semko Ebrahimi (Society of Diabetic Nephropathy Prevention, 2020)
Iodinated contrast agents are routinely used to diagnose a variety of diseases especially malignant tumors. They are crucial for accurate depiction of tumors, monitoring the response to treatment, and assessing possible recurrence of malignant lesions. Unfortunately, there are potential adverse effects associated with their administration. Metformin as an antidiabetic drug is prescribed widely. The drug is usually administered to control type II diabetes mellitus. One of the most important side effects of metformin is the possibility of lactate accumulation and occurrence of metforminassociated lactic acidosis (MALA), which develops under various circumstances including decreased renal function or concurrent use of toxic agents. Since, intravascular injection of iodinated contrast agents for radiologic purposes may result in kidney injury, it is suggested that metformin should be held in diabetic patients with renal failure before administration of contrast media and not to be taken by the patient again till 48 hours after the procedure and assessment of kidney function which should be normal.